Interactions of Laser-Induced Thermal Plume with Liquid–Air Interfaces in Straight-Chain Alcohols - Reese W. Anderson; Allison I. Anderson; Mark W. Gealy; Darin J. Ulness (Liquids)
This study investigates the dynamics of thermal plumes interacting with the liquid–air interface in straight-chain alcohols and their mixtures using a photothermal imaging technique based on thermal lensing. This method enables the indirect measurement of temperature gradients via changes in refractive index caused by localized laser heating. Employing a collimated laser beam, the results show the formation and evolution of cylindrical heated zones and their interactions with the liquid–air interface. The study reveals that, while some alcohols exhibit stable surface behaviors, others demonstrate complex dynamical behaviors, including strong stable steady-state oscillations. The findings contribute to understanding fluid dynamics in molecular liquids near their liquid–air interfaces.